Palladium–Schiff Base Complexes Encapsulated in Zeolite‑Y Host: Functionality Controlled by the Structure of a Guest Complex - Kumari, Susheela; Maddipoti, Karthik; Das, Bidisa; Ray, Saumi (Inorganic chemistry, 2019)
A series of palladium complexes of tetradendate Schiff base ligands L1 (N,N′-bis(salicylidene)phenylene-1,3-diamine) and its derivatives L2 and L3 have been synthesized by using the “flexible ligand method” within the supercage of zeolite-Y. These complexes in both their free and encapsulated states have been thoroughly characterized with the help of different characterization tools such as XRD, SEM-EDS, BET, thermal analysis, XPS, IR, and UV–vis spectroscopic studies. All these encapsulated complexes are identified with a dramatic red shift of the d–d transition in their electronic spectra when compared with their free states. Theoretical as well as experimental studies together suggest a substantial modification of the structural parameters of square planar Pd(II)–Schiff base complexes upon encapsulation within the supercage of zeolite-Y. Encapsulated complexes are also subject to show modified catalytic activities toward the Heck reaction. These heterogeneous catalysts can easily be separated from the reaction mixture and reused.